Pressão arterial em cães: uma revisão - Tebaldi, Mariana [UNESP] (2011)
The evaluation of blood pressure is an essential tool for veterinarian clinical practice and for monitoring anesthetized patients or patients in intensive care, because of its usefulness in diagnostics, treatment and monitoring of several diseases. Apart from the pathological factor, the blood pressure also suffers the influence of different variables, such as age, breed, gender, temperament (anxiety and stress especially during the treatment, “white coat syndrome”), disease state, physical activity and, with lower intensity, animal’s diet. One of the main indications of the evaluation of blood pressure is the observation of clinical changes resulting from hypertension in animals, which one is characterized by lesions in the nervous and cardiovascular systems, kidneys and eyes. Not least important, the evaluation of blood pressure is also essential in hypotensive states, which represent an imminent risk of death. The techniques used in measuring blood pressure correspond to invasive forms (direct) or non invasive (indirect), whose correlation has been the subject of study and improvement within the small animal clinic. Thus, the purpose of this review is emphasize the importance of measuring blood pressure within the veterinary clinic routine, studying the influence of variables associated or not with elevated blood pressure, comparing the different methods used to obtain the blood pressure